Transforming rice cultivation: exploring direct seeded rice (DSR) suitability in Haryana through geospatial technology - Srivastava, Amit; Yeggina, Pavan Kumar; Chall, Kranthi; Deb, Proloy; Sweta; Singh, Jasbir; Urfels, Anton (International Rice Research Institute, 2024)
Rice cultivation in India is traditionally water-intensive, requiring between 800-5000 liters of water per kilogram of rice. In Haryana, a key state for India's food security, the overuse of groundwater and significant greenhouse gas emissions from traditional puddled rice farming are major environmental concerns. Direct Seeded Rice (DSR) presents a promising alternative, offering water savings, reduced labor dependency, and lower GHG emissions. To optimize DSR's adoption, it's essential to identify suitable zones with the right soil, water, and climatic conditions. Geospatial technologies and site-specific analyses can enhance the precision of suitability mapping, enabling more sustainable agricultural practices in the region.